PENINGKATAN PRESTASI BELAJAR MELALUI METODE PEMBELAJARAN KOOPERATIF TIPE STAD TENTANG PERPINDAHAN PANAS DENGAN CARA RADIASI - Pujiati Indrawaningsih (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
The purpose of this study is to (1) improve student achievement in science subjects, the subject of heat transfer and (2) determine the effect of the STAD type cooperative learning model on the subject of heat transfer on student learning systems. Classroom action research (CAR) was conducted in 2 cycles, each cycle. The subjects of this study were grade VI students of SDN Karangbinangun Kec. Karangbinangun, Lamongan Regency with a total of 18 students. The improvement that can be observed from the application of STAD type cooperative learning methods is the teaching and learning process centered on student activities through the application of this method students are more active because of the pleasant learning atmosphere, easy to understand the material because it is assisted through concrete learning media, discussions, questions and answers and peer tutors . The results of the study were quite good, in the first cycle of 18 students, 13 students increased (72.2%), 5 students did not increase (18%). In the second cycle of 18 students, 16 students increased (88.8%), 2 students did not increase (11.2%).